2005
DOI: 10.1007/s11664-005-0204-4
|View full text |Cite
|
Sign up to set email alerts
|

Contact resistance and shear strength of the solder joints formed using Cu bumps capped with Sn or Ag/Sn layer

Abstract: Solder joints were successfully bonded by joining Ag/Sn/Cu bumps and Ag/Sn/Cu layers at 200°C for 30 sec under 20 MPa, 40 MPa, and 80 MPa using thermo-compression bonder. The solder joints were aged at 150°C up to 1000 h. The strength of the solder joints was measured by the shear test and the contact resistance was measured using four-point probe method. The microstructure of the solder joints and the fracture modes after shear test were analyzed by scanning electron microscopy (SEM) with the energy-dispersiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The results of this study are in agreement with the results of Lee et al [22] who have found that the electrical resistance of solder Ag/Sn/Cu joints decreased, whereas their shear strength joints increased with the aging time.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study are in agreement with the results of Lee et al [22] who have found that the electrical resistance of solder Ag/Sn/Cu joints decreased, whereas their shear strength joints increased with the aging time.…”
Section: Discussionsupporting
confidence: 93%
“…During cooling, a Cu 6 Sn 5 phase forms first in the Cu surface because the activation energy of the Cu 6 Sn 5 phase is lower than that of Cu 3 Sn IMC. [9][10][11]14 Typically, a Type I microstructure (Sn + Cu 6 Sn 5 ) is observed in the solder joints. When the liquid Sn is reacted with Cu at high temperature for a long time, Cu 3 Sn begins to form.…”
Section: Discussionmentioning
confidence: 99%
“…The shear strength of the solder joints was measured by shearing the test dies. 9,14 The microstructures of the solder joints before and after aging were analyzed using scanning electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ (4) A similar approach to hollow square model can be achieved. The maximum distance and minimum distance can be measured as shown in Figure 6.…”
Section: Quality Inspection Method: Torsion Test Screeningmentioning
confidence: 99%